2012
DOI: 10.1039/c2sm25068c
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of artificial microtubules

Abstract: Understanding the complex self-assembly of biomacromolecules is a major outstanding question. Microtubules are one example of a biopolymer that possesses characteristics quite distinct from standard synthetic polymers that are derived from its hierarchical structure. In order to understand how to design and build artificial polymers that possess features similar to those of microtubules, we have initially studied the self-assembly of model monomers into a tubule geometry. Our model monomer has a wedge shape wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 54 publications
0
41
0
Order By: Relevance
“…Mobile ions are sometimes included explicitly for additional realism, some of the CG water models have specific ion parameters . Very often, even less detailed representations of the solvent are employed, where all of the solvent effects are essentially parameterized into the existing pairwise bead–bead interactions, without a separate solvation term in the Hamiltonian.…”
Section: Coarse‐grained Water Modelsmentioning
confidence: 99%
“…Mobile ions are sometimes included explicitly for additional realism, some of the CG water models have specific ion parameters . Very often, even less detailed representations of the solvent are employed, where all of the solvent effects are essentially parameterized into the existing pairwise bead–bead interactions, without a separate solvation term in the Hamiltonian.…”
Section: Coarse‐grained Water Modelsmentioning
confidence: 99%
“…One surprise found in our previous simulations using the achiral M 0 is the preferential assembly of helical tubules with pitch 1 or even 2. [22] New results here show that tubules with pitch mismatching the monomer chirality still assemble even for chiral monomers. We found that one factor that can help suppress the mismatch and better control the tubule pitch is to make vertical binding stronger.…”
Section: Simulation Methodsmentioning
confidence: 76%
“…For example, molecular dynamics (MD) simulations using a wedge‐shaped monomer (Fig. a) have recently demonstrated that self‐assembly into tubule structures depends on key factors such as molecular orientation and the relative influences of both lateral (transverse to the tube) and vertical (along the tube length) molecular interaction strengths (Cheng et al, ; Cheng and Stevens ). MD has further shown that the pitch of the tubule can be controlled by the chirality of the monomer, but also that a twist deformation tends to yield a range of pitch values.…”
Section: Toward Artificial Microtubule Filamentsmentioning
confidence: 99%